Perbandingan Implementasi The Convention on The Elimination of All Forms of Discrimination Against Women (CEDAW) dalam Pemenuhan Hak Politik dan Ekonomi Perempuan di Arab Saudi dan India - Abdullah, Nurjannah; Hastira, Muhammad Fajhriyadi (Hasanuddin Journal of International Affairs, 2023)
The Convention on the Elimination of All Forms of Discrimination against Women (CEDAW) is a monumental document in the history of the development of the fulfillment of women's rights in the international world. This convention was born out of the problems of discrimination and inequality faced by women around the world. This article discusses the comparison of Saudi Arabia and India in implementing CEDAW by comparing each article that focuses on the fulfillment of women's rights in the political and economic fields. This article uses data collection and analysis methods in the form of library research with data analysis techniques in the form of qualitative data techniques. The results of this study show that each country in implementing an international regime is influenced by several factors ranging from internal actors and external actors. Furthermore, a comparison of the implementation of these two countries shows that Saudi Arabia is much more compliant with the CEDAW convention than India. ? The Convention on the Elimination of All Forms of Discrimination against Women (CEDAW) merupakan sebuah dokumen yang monumental dalam sejarah perkembangan pemenuhan hak perempuan di dunia internasional. Konvensi ini lahir dari adanya permasalahan diskriminasi dan kesenjangan yang sangat tinggi yang dihadapi oleh perempuan di seluruh dunia. Artikel ini membahas mengenai perbandingan dari Arab Saudi dan India dalam mengimplementasikan CEDAW dengan membandingkan setiap pasal yang berfokus pada pemenuhan hak perempuan dalam bidang politik dan ekonomi. Artikel ini menggunakan metode pengumpulan dan analisis data berupa telaah pustaka (library research) dengan teknik analisis data berupa teknik data kualitatif. Hasil dari penelitian ini menunjukan bahwa masing-masing negara dalam mengimplementasikan sebuah rezim internasional dipengaruhi oleh beberapa faktor mulai dari faktor internal maupun faktor eksternal. Lebih lanjut, perbandingan implementasi kedua negara ini menunjukan bahwa Arab Saudi jauh lebih patuh terhadap konvensi CEDAW dibandingkan dengan India.